Lazer, cinema e modernidade: um estudo sobre a exibição cinematográfica em Montes Claros (MG) - 1900-1940 - Carvalho, Jailson Dias (2010)
The subject of this study, Leisure, cinema and modernity: a study on the cinema in Montes Claros (MG) - 1900-1940 , refers to an investigation about the genesis of the exhibition circuit of cinema in Montes Claros and about the different ways of leisure which were found on the public space of the abovementioned town. Another purpose of this research was to reflect on how modernity was configured in this county. The sources used in this research were of different origins. From a range of sources, one could notice that throughout the 19th century, between 1840 and 1880, Montes Claros had an important role in regional trade. Thus, the opening of new streets, the fruitful trade with neighbor cities, the installation of plant tissues at Cedro, the arrival of the telegraph and the display of the cosmorama (among other situations and events in the final years of the 19th century) represented the preeminence of urban underway in Montes Claros. However these different events had not patented merely economic changes. Concomitant to all these changes, it was found that some circus companies, itinerant theater groups (called mambembes ) and performances of prestidigitation which came upon the public scene of the small town revealed that the region of Montes Claros had no artistic isolation. The performances of the mamembes had prepared the public for the advent of optical and audio entertainment, and also for the cinema at the dawn of the 20th century, because they were close to the seventh art, since they arouse the shock, surprise, enthusiasm, excitement and rush. All these features correspond, thus, to stimuli similar to those coming from modern changes, such as traffic, machinery, transportation, city lights, urban clusters and different noises. The mediation of cinema and the inauguration of the theaters along with the building improvements and installation of modern projection equipment, the progress in Montes Claros began to be operated and became active. Thus, through the discourse of newspapers, the cinema became a reference of what was modern , civilized , progress and also a way of identification in order to evaluate the city as a northeastern metropolis , a northern metropolis , a polite society . Finally, one could notice that in the current economic environment of the cinema, which is characterized by the concentration of the theaters and of the economic resources, there is a small chance, especially in Montes Claros, of existing a traditional familiar exhibitor, who decides to build or adapt a place to film exhibitions and, for this purpose, signs a contract with a company or distributor responsible for equipping the film exhibitor house with films.